Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

When is $1^5 + 2^5 + \ldots + n^5$ a square? I found that this happens sometimes: $n=13$ gives $1001^2$, $n=133$ gives $9712992^2$ and $n=1321$ gives $942162299^2$.

I feel that the identity$$\displaystyle\sum_{i=1}^n i^5 = \tfrac{1}{12}[2n^6+6n^5+5n^4-n^2]$$ will be useful, since it's all square powers except one.. but I see no way to connect that.

share|improve this question
1  
The question you ask is very similar to the classic cannonball problem. See en.wikipedia.org/wiki/Edouard_Lucas, mathworld.wolfram.com/CannonballProblem.html. –  Alex J Best Oct 19 '12 at 18:19
4  
The cannonball problem is integer points on an elliptic curve. This problem is a Pell equation, a much simpler thing. –  zyx Oct 19 '12 at 19:15
1  
+1 Good question. –  AD. Oct 24 '12 at 14:21
add comment

5 Answers 5

up vote 23 down vote accepted
+100

The general solution to $$m^2 = \frac{1}{12}(2n^6+6n^5+5n^4−n^2)$$ is $$m = \frac{n(n+1)}{2} y, \quad n = (x-1)/2$$ where $$x+\sqrt{6} y = (3+\sqrt{6}) (5+2 \sqrt{6})^k$$ for some integer $k$. Here are the first few values $$\begin{array}{|r|l|l|l|l|} \hline k& x & y & n & m\\ \hline 0& 3& 1& 1& 1 \\ 1& 27& 11& 13& 1001\\ 2& 267& 109& 133& 971299 \\ 3& 2643& 1079& 1321& 942162299 \\ 4& 26163& 10681& 13081& 913896491101\\ \hline \end{array}$$

The values of $x$, $y$ obey the recursions $$x_{k+1} =10 x_k - x_{k-1}$$ $$y_{k+1} =10 y_k - y_{k-1}$$ There are more complicated recursions for $n$ and $m$, but I didn't work them out.


As several answers have already done, start by factoring $$m^2 = \frac{1}{12}(2n^6+6n^5+5n^4−n^2) = \frac{1}{3} \left( \frac{n(n+1)}{2} \right)^2 (2n^2+2n-1)$$ So $$2n^2 + 2n -1 = 3 y^2$$ where $y = m \left( \frac{n(n+1)}{2} \right)^{-1}$.

Completing the square: $$(2n+1)^2 - 3 = 6 y^2.$$ So we want to solve $$x^2-6 y^2 = 3$$ with $x$ odd.

This is a Pell like equation. The best way to think about Pell's equations is to think in the ring $\mathbb{Z}[\sqrt{6}]$. For an element $a+b \sqrt{6}$ in this ring, the norm $N(a+b \sqrt{6})$ is $a^2-6 b^2$. Norm is multiplicative, meaning that $N((a_1 + b_1 \sqrt{6}) (a_2 + b_2 \sqrt{6})) = N(a_1+b_1\sqrt{6}) N(a_2 + b_2 \sqrt{6})$. We want to find elements $x+y\sqrt{6}$ with $N(x+y\sqrt{6})=3$.

Notice that $N(5+2 \sqrt{6}) = 1$, so, if $N(x+y \sqrt{6})=3$, then $N((x+y \sqrt{6}) (5+2 \sqrt{6})^k)=3$ for any integer $k$. We will eventually be showing that all solutions to $N(x+y\sqrt{6})=3$ are of the form $x+y \sqrt{6} = \pm (3+\sqrt{6})(5+2 \sqrt{6})^k$.

In general, for $D>0$ any nonsquare, there is always some $(u_0,v_0)$ (the fundamental solution of Pell's equation) so that all solutions to $N(u+v \sqrt{D})=1$ are of the form $u+v \sqrt{D} = \pm (u_0 + v_0 \sqrt{D})^n$. In our setting, $(u_0, v_0) = (2,5)$. For any $K$, there finitely many pairs $(x_1, y_1)$, $(x_2, y_2)$, ..., $(x_r,y_r)$ such that all solutions to $N(x+y \sqrt{D})=K$ are of the form $x+y \sqrt{D} = (x_i+y_i \sqrt{D}) (u_0+v_0 \sqrt{D})^k$ for some $i$ and $k$.

We want to show that, in our case, $r=1$ and we can take $(x_1,y_1) = (3,1)$.

Brute force approach: Let $(x,y)$ be a solution to $N(x+y \sqrt{6}) = 3$ with $x$ and $y>0$. Find a nonnegative integer $k$ such that $$(5+2 \sqrt{6})^k < x+y \sqrt{6} < (5+2 \sqrt{6})^{k+1}.$$ This is always possible, since $\lim_{k \to \infty} (5+2 \sqrt{6})^k=\infty$. Notice that $(5+2 \sqrt{6})^{-1} = 5-2 \sqrt{6}$. So the coefficients of $(x+y \sqrt{6})(5+2 \sqrt{6})^{-k}$ are integers; call them $x_0$ and $y_0$. So $$1 < x_0+y_0 \sqrt{6} < 5+2 \sqrt{6} \ \mbox{and} \ N(x_0+y_0 \sqrt{6})=3$$ Also, we have $$x_0-y_0 \sqrt{6} = 3/(x_0+y_0 \sqrt{6})$$ so $$3/(5+2 \sqrt{6}) < x_0-y_0 \sqrt{6} < 3.$$ Adding these together $$\frac{1}{2} \left( 1+\frac{3}{5+2 \sqrt{6}} \right) < x_0 < \frac{1}{2} \left( (5+2 \sqrt{6})+3 \right)$$ or $$0.6 < x_0 < 5.9.$$ Trying $x_0 = 1$, $2$, $3$, $4$, $5$, we quickly discover the only possibility is $x_0=3$, $y_0=1$. So $x+y \sqrt{6} = (3+\sqrt{6})(5+2 \sqrt{6})^k$.

Slick solution Let $I$ be the ideal generated by $x+y \sqrt{6}$ in the ring $\mathbb{Z}[\sqrt{6}]$. Then $\mathbb{Z}[\sqrt{6}]/I$ has order $3$, so $I$ is a prime ideal containing $(3)$. The prime $3$ ramifies in $\mathbb{Z}[\sqrt{6}]$ so there is only one such prime. Clearly, $(3+\sqrt{6})$ is such a prime, so any other solution to $N(x+y \sqrt{6})=3$ must be such that the ideals $(x+y \sqrt{6})$ and $(3+\sqrt{6})$ are equal. So $x+y \sqrt{6} = (3+\sqrt{6})*\mbox{unit}$, and the units in this ring are $\pm (5+2\sqrt{6})^k$.

Where the recursions come from: Let $u = 5+2 \sqrt{6}$. The minimial polynomial of $u$ is $u^2-10u+1=0$. So $u^{k+1} = 10 u^k -u^{k-1}$, implying that $(5+2 \sqrt{6})u^{k+1} = 10(5+2 \sqrt{6})u^k -(5+2 \sqrt{6})u^{k-1}$ and thus that $(x_{k+1} + y_{k+1} \sqrt{6}) = 10(x_k + y_k \sqrt{6}) - (x_{k-1} + y_{k-1} \sqrt{6})$.

share|improve this answer
add comment

If $$a=1+2+3+\cdots+n$$ then $$ 1^5+2^5+3^5+\cdots+n^5 = \frac{4a^3-a^2}{3}, $$ so now the question is: when is that a square?

share|improve this answer
2  
Isn't that an elliptic curve? –  sperners lemma Oct 19 '12 at 18:39
1  
As an elliptic curve it is singular, since $4a^3-a^2$ has a double root at $0$. However, I don't think this is the best approach, because once you find the solutions to $y^2= (4a^3-a^2)/3$, you will still have to figure out which of those solutions have $a$ triangular. –  David Speyer Oct 19 '12 at 18:54
3  
And that is a square precisely when $\frac{4a-1}{3}$ is a square, so you don't really need an elliptic curve. –  Thomas Andrews Oct 19 '12 at 19:35
6  
It narrows down to solving $(2n+1)^2-6y^2 = 3$, I think. –  Thomas Andrews Oct 19 '12 at 19:37
1  
@ThomasAndrews Why not transform your comments into answer? You could derive(+1) a Pell-equation and it can be considered as completely discussed so you answered the original question completely. –  vesszabo Oct 24 '12 at 10:20
show 1 more comment

This is OEIS A031138, which lists some more and says $a(n) =11\cdot(a(n-1)-a(n-2)) + a(n-3) \\ a(n)=-1/2+((3-\sqrt 6)/4)\cdot(5+2\sqrt 6)^n+((3+\sqrt 6)/4)\cdot(5-2\sqrt 6)^n$

share|improve this answer
2  
Wait, doesn't it say: a(n)=-1/2+((3-sqrt(6))/4)*(5+2sqrt(6))^n+((3+sqrt(6))/4)*(5-2sqrt(6))^n? –  Thomas Andrews Oct 19 '12 at 18:20
    
@ThomasAndrews: missed it. Now added. Thanks –  Ross Millikan Oct 19 '12 at 18:25
    
great find. I am curious about the soundness and completeness of that recurrence relation. –  sperners lemma Oct 19 '12 at 18:25
add comment

If we factor the power sum identity we find the problem equivalent to $$m^2 = \tfrac{1}{3}\left[\frac{n(n + 1)}{2}\right]^2(2n^2 + 2n - 1)$$ or $$m'^2 = \tfrac{1}{3}( 2n^2 + 2n - 1 )$$ this is an integer hence the $1/3$ implies $n\equiv 1\pmod 3$ so let $n = 1 + 3n'$ to get $$m'^2 = 6n'^2 + 6n' + 1$$ but I don't know what now.

The RHS can be described by the recurrence relation: $a_0 = 1$, $a_{n+1} = a_n + 12 n$. Is there any theory about recurrences with '$n$' in them I might be able to use to tell when it takes on square values?

Completing the square like here gives $3(2n'+1)^2 - 2m'^2 = 1$ almost a pell equation with the condition one value is odd.

share|improve this answer
2  
This is a good thought. Now I would complete the square in reverse to get $m'^2=(3n'+1)^2-3n'^2$ so $m'^2=((3-\sqrt 3)n+1)((3+ \sqrt 3)n'+1)$ This feels like a similar structure to the Pell equation, so those expert in its nuances may have more to say. The fact that OEIS cites a recurrence supports that view, but I am stuck as well. –  Ross Millikan Oct 22 '12 at 4:05
    
@RossMillikan, thanks but I'm still stuck. I thnk it's progress though. –  sperners lemma Oct 23 '12 at 20:00
add comment

$$1^5 + 2^5 + ... + n^5 = \frac{1}{12} n^2 (n+1)^2 (2 n^2+2 n-1) $$ Now we need to solve $$\frac{1}{12} n^2 (n+1)^2 (2 n^2+2 n-1) $$ is a perfect square $$\iff\frac{2 n^2+2 n-1}{12} = k^2$$ [do some thing here] I don't know how to solve more

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.